2016
DOI: 10.1007/978-3-319-47874-6_13
|View full text |Cite
|
Sign up to set email alerts
|

Social Contribution Settings and Newcomer Retention in Humanitarian Crowd Mapping

Abstract: Abstract. Organisers of crowd mapping initiatives seek to identify practices that foster an active contributor community. Theory suggests that social contribution settings can provide important support functions for newcomers, yet to date there are no empirical studies of such an effect. We present the first study that evaluates the relationship between colocated practice and newcomer retention in a crowd mapping community, involving hundreds of first-time participants. We find that certain settings are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Imports, for example, were found to introduce quality issues that affect the feasibility of future imports (Zielstra et al, 2013) and to have a limited effect on the behavior of established mappers or on retaining new users (Juhász & Hochmair, 2018). Studies of humanitarian remote mapping efforts show that coordination practices and event frequency are important in engaging newcomers during events and retaining them (Dittus, Quattrone, & Capra, 2016a, 2016b). Yet, apart from high-profile cases, these events generally rely on a relatively stable community of experienced mappers (Dittus et al, 2017).…”
Section: Org Anized Ac Tivitie S Within the Os M Projec Tmentioning
confidence: 99%
“…Imports, for example, were found to introduce quality issues that affect the feasibility of future imports (Zielstra et al, 2013) and to have a limited effect on the behavior of established mappers or on retaining new users (Juhász & Hochmair, 2018). Studies of humanitarian remote mapping efforts show that coordination practices and event frequency are important in engaging newcomers during events and retaining them (Dittus, Quattrone, & Capra, 2016a, 2016b). Yet, apart from high-profile cases, these events generally rely on a relatively stable community of experienced mappers (Dittus et al, 2017).…”
Section: Org Anized Ac Tivitie S Within the Os M Projec Tmentioning
confidence: 99%
“…Voluntary contributors digitize maps (with the location of human settlements, roads, rivers, etc.) on satellite images collected in the field in response to natural disasters, for example, Typhoon Haiyan in the Philippines, the earthquake in Nepal in early 2015 and other disasters where humanitarian aid teams required updated maps to coordinate their work [174]. Humanitarian OpenStreetMap Team (HOT) [175], Mapswipe [176], and Missing Maps [171] have coordinated thousands of volunteers in the creation of maps for humanitarian purposes [174].…”
Section: Sensing Systems and Solicited Crowd-sourcingmentioning
confidence: 99%
“…on satellite images collected in the field in response to natural disasters, for example, Typhoon Haiyan in the Philippines, the earthquake in Nepal in early 2015 and other disasters where humanitarian aid teams required updated maps to coordinate their work [174]. Humanitarian OpenStreetMap Team (HOT) [175], Mapswipe [176], and Missing Maps [171] have coordinated thousands of volunteers in the creation of maps for humanitarian purposes [174]. Unfortunately, the accuracy of these programs is debatable [177,178], but additional deep learning algorithms can trace these errors [175].…”
Section: Sensing Systems and Solicited Crowd-sourcingmentioning
confidence: 99%
“…The findings of Hristova et al [18] suggest that employing social events as the dominant mode of recruiting OSM contributors might be insufficient to eliminate data gaps in OSM. Mapping parties and mapathons help generate data, but most mappers appear to be unlikely to continue mapping on their own, even if they may be motivated to pursue mapping [7,19]. In a study of contributors' withdrawal from OSM, Bégin, Devillers, & Roche [20] discovered that a large majority of participants withdraw during a short "assessment" phase in which contributors explored the project to determine if they would engage in the long term.…”
Section: Related Workmentioning
confidence: 99%
“…Although the importance of such mapping events is well recognized within the OSM community, several studies have exposed their limitations in sustaining contributions from participants beyond the event. Dittus et al [7] found that many participants who were "activated" during mapping events discontinued mapping when they returned home. These findings indicate that engaging potential contributors only for the duration of a mapping event results in minimal data generation and contributor retention, severely limiting the potential of engaging contributors to generate geospatial data and reducing the coverage, quality and detailed attributes of the data in OSM as a result.…”
Section: Introductionmentioning
confidence: 99%